Role of Higher Education in Solving Global Problems - Maria Jakubik (International School for Social and Business Studies, 2022)
Purpose: The global problems of the world need urgent and sustainable solutions and actions. This conceptual paper seeks to answer the question: How can higher education develop authentic and responsible citizens who will be able to act and solve global problems? Study design/methodology/approach: Building on a range of selected literature from psychology, philosophy, education, and leadership, the paper first clarifies the concepts of authenticity and responsibility, then, it focuses on the role of higher education in supporting learners to develop their personal authenticity and strengthen their responsibility for others and for their environment. Findings: The findings show that it is possible to become both authentic and responsible person and higher education curriculum and pedagogy play a decisive role in it. Originality/value: The paper contributes to the discourses about the role of higher education in solving global problems. It also offers implications for higher educational researchers, learners and educators, university curriculum and pedagogy.